Understanding Hezbollah : the hegemony of resistance - Kanaaneh, Abed T. (Contemporary issues in the Middle East., 2021)
"This book is concerned with the activism of the Lebanese Hizbullah movement towards strengthening its status in the Lebanese arena. It focuses on the Hizbullah's contribution to the development of the concept of Muqawamah (resistance) as part of a counter-hegemonic project"--